Q. 215.0( 3 Votes )

For the mat

Answer :

A =


A3 = A2.A


A2 =


=


A2.A =


=


=


Now, A3 – 6A2 + 5A + 11I


+ 11


=


=


=


Thus, A3 – 6A2 + 5A + 11I


Now, (AAA) A – 1. – 6(A.A) A – 1 + 5.A A – 1 + 11I.A – 1 = 0


AA(A – 1A) – 6A(A – 1A) + 5(A – 1A) = – 1(A – 1I)


A2 – 6A + 5I = 11 A – 1


= A – 1 =


Now,


A2 – 6A + 5I


=


=


=


=


Hence, A – 1 =

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Prove the followiMathematics - Board Papers